1989
DOI: 10.2136/sssaj1989.03615995005300060048x
|View full text |Cite
|
Sign up to set email alerts
|

Pedon Distribution of Minerals in Coastal Plain Paleudults

Abstract: Mineral distributions in three Florida Paleudults were investigated with respect to particle size, horizon, depth, and location within the soil matrix. Mineralogy of sand, silt, and clay was determined using optical microscopy, x‐ray diffraction, and thermal analysis. Also, mineralogy of sand‐grain coatings was compared with intergrain matrix material. Elemental‐oxide composition of siltsized phyllosilicate grains was determined by electron microprobe analysis. Sand fractions consisted mainly of quartz, with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A mica precursor is consistent with the prevalence of HIV in sandy horizons (Cabrera et al, 1989;Harris et aL, 1989). Mica, as a relatively coarse-grained phyllosilicate in sediments, would likely have weathered in place during the period when colloidal components such as kaolinite eluviated to deeper zones.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…A mica precursor is consistent with the prevalence of HIV in sandy horizons (Cabrera et al, 1989;Harris et aL, 1989). Mica, as a relatively coarse-grained phyllosilicate in sediments, would likely have weathered in place during the period when colloidal components such as kaolinite eluviated to deeper zones.…”
Section: Resultsmentioning
confidence: 56%
“…It tends to be particularly abundant in near-surface horizons, rivaling kaolinite as the primary clay component (Bryant and Dixon, 1963;Carlisle and Zelazny, 1973;Harris et al, 1989;Rich, 1968a;Rich and Obenshain, 1955). Its properties are important to consider given its prevalence in the root zone, its reactivity relative to other mineral components present, and its potential for selective cation sorption (Rich and Black, 1964;Rich, 1968b).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms and conditions of polymer formation within interlayers of vermiculite (Rich, 1960;Hsu and Bates, t 964) and montmoriUonite (Shen and Rich, 1962;Brydon and Kodama, 1966) have been studied via artificial synthesis of polymers within interlayers. Many soils of humid regions (i.e., the southeastern U.S.) contain abundant HIV in clay fractions (Fiskell and Perkins, 1970;Carlisle et al, 1978Carlisle et al, , 1981Carlisle et al, , 1985Carlisle et al, , 1988, particularly in near-surface horizons (Rich and Obenshain, 1955;Bryant and Dixon, 1963;Rich, 1968;Carlisle and Zelazny, 1973;Harris et aL, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Rich (1968) suggested that relatively acid (pH 4.5 to 5.8) -oxidizing conditions in low organic matter environments with seasonal wetting and drying, conditions commonly found in upland, well drained settings of the Southeastern U.S., promote hydroxyinterlayered vermiculite formation. Several studies have noted the enrichment in near-surface horizons and sandy epipedons of hydroxyinterlayered vermiculite, and its relative depletion with corresponding increases in kaolinite either with depth and/or across eluvial/illuvial boundaries (Rich and Obenshain, 1955;Harris et al, 1987;Harris et al, 1989;Cabrera-Martinez et al, 1989). As an example, the depth distribution of gibbsite, kaolinite, and hydroxy-interlayered vermiculite are shown for representative Alabama Piedmont (Kanhapludult) and Coastal Plain (Kandiudult) soils ( Fig.…”
Section: Introductionmentioning
confidence: 99%